Application of the Zero Defect Theory in Medical Record Management. (June 2014) - Tang, Ruifan; Lv, Wanxia; Dai, Chunxia; Liang, Ruiyan; Lu, Xiaolan
Abstract Objective. To pursue and reach the quality goal of zero defects and to further improve the quality of medical record management. Method. Apply the theory of zero defects to medical record management; the zero defect quality goal was gradually reached through total involvement in education, the construction of a professional team, improvement in the quality control system, quality standardization, removal of out-of-control quality problems, and continuous quality improvement. Results. After the implementation of zero-defect management, the accuracy of recovering medical records has increased from 97.1% to 100%; the accuracy of sorting discharge records has increased from 93.5% to 99.8%; the accuracy of medical record information processing has increased from 95.8% to 99.2%; and the accuracy of binding discharge records has increased from 99.8% to 100%; the on-the-shelf accuracy of medical records has increased from 99.9% to 100%; in two years, there has been no missing of medical records or filing errors; the service efficiency and accuracy of medical records have been increased. Each quality management measure was implemented, medical record management was performed properly, and the quality of medical record management was further improved. Conclusion. The zero defect theory is applicable to medical record management, and serves as an effective approach to promoting the advancement and scientific method of medical record management.